The Flu Epidemic in Russia in the 2013 - 2014 Season: Etiology, Antigenic Properties of Hemagglutinin and Neuraminidase Activity - T. G. Lobova; D. M. Danilenko; N. I. Konovalova; E. M. Yeropkina; S. M. Shchekanova; P. A. Petrova; E. G. Kornilova; M. Yu. Yeropkin (Эпидемиология и вакцинопрофилактика)
The present study describes etiological structure of population of influenza viruses that circulated in Russian Federation in epidemic season 2013 - 2014. It was shown that from 495 isolates influenza A(H1N1)pdm09 viruses comprise 46.3%, influenza A(H3N2) - 44.2% and influenza B - 9.5% with domination of Yamagata lineage. Comparative study of antigenic properties of major influenza surface protein hemagglutinin was conducted based on the results of HI test and three-dimensional antigenic cartography. The correspondence between WHO recommended strains for vaccine composition 2013 - 2014 and Russian strains of the analyzed period was shown. Quantitative analysis of enzyme activity of the second surface influenza protein - neuraminidase - for 203 influenza strains differing in year of isolation, antigenic composition and host specificity showed that the highest activity was registered for the neuraminidase of A(H5N1) influenza viruses. In general, the activity of N1 neuraminidase was higher than that of N2 subtype, but sufficient individual variation of NA activity within the subtype could be registered.